O50 "the metadebrief club" – our experiences in developing a structured analysis of simulation debriefing and a safe learning environment for faculty staff development. (31st December 2017) - O'Shea, C; Pugh, D; Schnieke-Kind, C
Abstract : Context: Debriefing is fundamental to effective learning in medical simulation. Whilst efforts to improve the fidelity of simulated scenarios are widespread, there is less research aiming at improving the process of debriefing itself. We as a faculty wanted to develop a safe learning environment where we could review our debrief footage with the goal of sharing best practice and improving the quality of teaching delivered. We outline our experiences with developing a structured analysis of debriefing ("metadebriefing"), the establishment of this within NHS Lothian, and exploring the potential of this technique to improve our own practice. Methodology: We deliver approximately 200 simulation sessions to Foundation doctors within NHS Lothian over the 2016 – 2017 academic year. Within these, three clinical scenarios are each followed by a recorded debrief. Participants and facilitators rate each debrief using a standardised feedback tool. A once weekly metadebrief is held, where debrief footage is reviewed. During the metadebrief, all participants review footage together offering comment and analysis throughout. A formal 'stages of debriefing tool' was developed to explore the amount of time spent on stages within the debrief, and to assess whether set learning objectives were delivered (see Figure 1). An agreement was made amongst members to maintain a safe learning environment, with format and venue chosen to facilitate this. After each metadebrief, suggestions for future debriefing practice are produced for each debriefer. These are trialled at their next simulation session and the process repeated. Participant and facilitator feedback was ultimately reviewed to explore whether this practice improved our performance. Results: The process of metadebriefing has led to the generation of a safe learning space in NHS Lothian for faculty members to share their practices. The experiences of attendees has been universally positive. Self and peer-reported assessments of debriefing for the founding members have improved since the inception of this process, whilst continuing to deliver the learning objectives for the sessions. We shall present data for the entire academic year upon its completion, demonstrating the impact this has had on our practice. Conclusions and Recommendations: We have found metadebriefing to improve our own practice in delivering effective simulation. A space for faculty and peers to evaluate their debriefing in Lothian has been created, in a friendly and non-judgemental environment. We are now creating open metadebriefing meetings to create a sustainable platform for healthcare professionals involved in delivering simulation in Lothian.